ESTIMASI CADANGAN BIOMASSA PADA POHON GAHARU (Aquilaria malaccensis Lamk.) BERUMUR 14 TAHUN DI HUTAN PENDIDIKAN FAHUTAN UNMUL (HPFU) SAMARINDA KALIMANTAN TIMUR - Mirna Mirna; Rita Diana; Deddy Hardiyanto; Sidraha Kawaqib Putra (ULIN: Jurnal Hutan Tropis, 2019)
Agarwood Tree is one of the important species of tree that produces Gaharu resin. The aim of this research was to determine the tree physical condition, tree health, and its biomass value. The research was examined in Education Forest of Mulawarman University Samarinda East Borneo. The method used for this research was purposive sampling, which purposely chooses the tree (Aquilaria malaccensis Lamk) as much as 40 trees. Whereas biomass value using three Allometrik equations with different parameters, obtained with the biggest biomass value using tree diameter, wood density, and tree length. Furthermore, the second biggest biomass value using two parameters of tree diameter and wood density, while the smallest biomass value using one parameter equation which was tree diameter.